Introduction: beyond anthropocentrism, changing practices and the politics of 'nature' - Alexander Koensler; Cristina Papa (Journal of Political Ecology, 2013)
In this introduction to a Special Section, we outline three recent interrelated research tendencies with regard to how to understand the practices and politics of 'nature': 1) a major attention towards non-anthropocentric environmental ideologies; 2) more complex analyses of environmental movements; and finally, 3) attention to unconventional every-day practices of environmental justice. In all three tendencies, we argue, a renewed attention to socio-economic power relations of the wider context becomes crucial for a better understanding of environmental dynamics. Ethnographically engaged studies from the European context offer examples of how it becomes possible to assess the impact of new grass-root practices, to pay attention to good micropractices, and understand the unexpected outcomes of the engagement with nature.